Timequake - Vonnegut, Kurt. (London : Vintage, 1998)
Intersperses a story about a glitch in the space-time continuum that forces people to relive the ten years between February 17, 1991 to February 13, 2001 exactly as they did the first time, with Vonnegut's thoughts and experiences during the summer and autumn of 1996.
Young Adult.
Young Adult
Keywords: Vonnegut, Kurt -- Fiction; Vonnegut, Kurt -- Fiction; Space and time -- Fiction; Science fiction; Space and time -- Fiction